Analysis of the Z-Score Model in Predicting Financial Distress and Its Impact on Firm Value - Tridara, Virnanda Nur Aini (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to examine the effect of financial distress, measured using the Altman Z-Score model, on the value of the firm in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2022-2024. The value of the firm is proxied by Tobin's Q ratio. This study uses a quantitative approach with secondary data in the form of annual financial reports. The sampling technique used purposive sampling, resulting in 53 companies with a total of 159 observations. The results show that the Altman Z-Score has a positive and significant effect on the value of the firm. This finding indicates that healthier financial conditions increase investor confidence and the market value of the company. Thus, the Altman Z-Score model is relevant as a tool for predicting financial distress and as a basis for decision-making.